The meaning of superhero comic books - Wandtke, Terrence R. (McFarland & Co., 2012)
"This volume details how the workings of the superhero comics industry and the conventions of the medium have developed a culture like that of traditional epic storytelling. By revealing how contemporary superhero comics connect traditional aesthetics and postmodern theories, this work explains why the superhero comic book flourishes in the "new traditional" shape of the digital age"--Provided by publisher.